The CROWN Initiative: journal editors invite researchers to develop core outcomes in women's health. (September 2014) - Leese, Henry
Abstract Human Fertility is pleased to support the 'CROWN' initiative outlined below, whose aim is 'to develop core outcomes in women's health'. The editorial, which was unanimously adopted by our Editorial Board is being published by more than 50 gynaecology-obstetrics and related journals. We commend it to all our readers